Monitoring a New England Cottontail Reintroduction with Noninvasive Genetic Sampling - Melissa L. Bauer; Brett Ferry; Heidi Holman; Adrienne I. Kovach (Wildlife Society Bulletin)
ABSTRACT Careful monitoring of reintroduced threatened species is essential for informing conservation strategies and evaluating reintroduction efforts in an adaptive management context. We used noninvasive genetic sampling to monitor a reintroduction of a threatened shrubland specialist, the New England cottontail (Sylvilagus transitionalis), in southeastern New Hampshire, USA. We monitored the apparent survival and breeding success of founder individuals and tracked changes in population size and genetic diversity for 5 years following an initial reintroduction in 2013. We released 42 rabbits, documented 29 unique offspring in years following releases through noninvasive surveys, and identified 6 founder individuals and 9 recruited offspring that bred. Apparent survival of founders was variable and greatest in the first year of the reintroduction. Predation was the primary cause of mortality and greatest in the first month after release and after heavy snowfall. Population size remained small but relatively stable until a stochastic decline in the fourth year following reintroduction, followed by a slight rebound after population augmentation and offspring production by wild‐born rabbits. Genetic diversity increased after the initial founders with diverse genetic backgrounds were released and then they and their subsequent offspring bred. We documented successful dispersal 700 m from the release site to a high‐quality patch of habitat, which remained occupied throughout the study. For New England cottontail reintroductions to be successful in the long term, releases will be needed at multiple patches within dispersal distance, and habitat corridors need to be restored among patches to create a functioning metapopulation. For small or isolated reintroduced populations, continued intensive monitoring is needed to detect stochastic declines in population size or changes in sex ratios and guide subsequent management reactions via additional reintroductions or population augmentations. Noninvasive genetic sampling is a valuable tool to monitor reintroductions of the New England cottontail and other threatened species to provide managers with detailed information to inform decision‐making in an adaptive management framework. © 2020 The Wildlife Society.